Radiologische Responsebeurteilung moderner Immuntherapien mithilfe von iRECIST - Persigehl, Thorsten; Pöppel, Thorsten Dirk; Sedlaczek, Oliver (Der Radiologe, 2017)
Clinical/methodical issueModern immunotherapies in oncology show tumor response patterns differing from conventional chemotherapies including initial pseudo-progression.Standard radiological methodsResponse evaluation criteria in solid tumors (RECIST 1.1) represent the currently most used response criteria for conventional chemotherapy of solid tumors. However, atypical response patterns of immunotherapies are not correctly classified using RECIST 1.1 so that the effectiveness is also incorrectly interpreted.Methodical innovationsIn order to correctly interpret these atypical response patterns, special immune-related response criteria in solid tumors (iRECIST) have been published. In contrast to RECIST 1.1 according to iRECIST an initially unconfirmed progressive disease (iUPD) requires confirmation (iCPD) in clinically stable patients by subsequent control imaging after 4-8 weeks. New lesions are separately assessed within iRECIST.PerformanceThe iRECIST procedure allows a standardized objective assessment of a possible pseudo-progression which can occur in up to 10% of cases depending on the immunomodulating drug and tumor entity.AchievementsIn principle, iRECIST was developed only for usage in trials testing modern immunotherapeutics.Practical recommendationsThe iRECIST procedure might also be helpful as an additional objective response criterium for clinical treatment decisions, taking the limitations into account.
Gesehen am 24.07.2018